A agricultura familiar frente às políticas de crédito rural: o papel do PRONAF na produção orgânica e agroecológica em Santana do Livramento/RS - Pinheiro, Gabriel Araujo (2025)
Family farming plays a strategic role in food production and promoting sustainability in Brazil. However, it continues to face structural challenges, such as unequal access to rural credit and little institutional appreciation of sustainable practices. Among existing public policies, the National Program for Strengthening Family Farming (Pronaf) stands out as the main financing instrument for this social category, although it has distortions that compromise its effectiveness, especially with regard to the specific line for agroecological production, Pronaf Agroecology. Given this, this research aimed to analyze Pronaf's contribution to organic and agroecological food production in the municipality of Santana do Livramento/RS. Specifically, it sought to: i) present access to resources and contracts from Pronaf total and Pronaf Agroecology at the national, state, and municipal levels; ii) investigate the role of Pronaf and Pronaf Agroecology in the production of organic and agroecological foods; iii) list the obstacles and challenges of credit for agroecological production. Methodologically, the research is descriptive and exploratory in nature, adopting a mixed-method approach. The quantitative stage consisted of analyzing secondary data from the Central Bank of Brazil, covering access to Pronaf in Brazil, Rio Grande do Sul, and Santana do Livramento between 2013 and 2023, as well as specific data from Pronaf Agroecologia at the national level, in the Southern Region and in the state of Rio Grande do Sul, from 2015 to 2023. For the qualitative stage, semi-structured interviews were conducted with six agroecological family farmers and four development agents. The interviews were analyzed using thematic categories, with fourteen categories identified among farmers—seven related to production and marketing and seven to access to credit—and thirteen categories based on the statements of development agents, referring to their perceptions of agroecological family farming as a whole. The results of the research indicate that Pronaf continues to reproduce concentrating dynamics by directing most of the financing to a limited number of activities, with emphasis on cattle ranching and soybean cultivation in the research location, Santana do Livramento, whose credit volume grew over the period analyzed, while Pronaf Agroecology did not provide any access in the municipality during the period. In Santana do Livramento, there is a significant presence of technical assistance focused on agroecological production. However, family farmers express a desire for greater local coordination, access to financing compatible with the local agroecological reality, and the need to reduce the bureaucratic obstacles that hinder access to public policies.